Sex determination using direct photography technique : a mobile-phone camera : a digital approach for lip prints analysis in Malaysian Malay population (Klang Valley) - Noor Hazfalinda Hamzah; Yee Ze Goh; Gina Francesca Gabriel; Khairul Osman; Nur Mahiza Md Isa (Penerbit Universiti Kebangsaan Malaysia, 2023)
Cheiloscopy may not be as well-known as other techniques of identification, such as fingerprint or DNA analysis, but it has its own impact in the appropriate circumstances. Cheiloscopy has been recognized as an important tool for human identification. A manual approach of studying lip prints was utilised by many researchers (magnifying glasses). Nonetheless, the current study relied solely on a mobile phone camera to visually capture lip prints for sex determination. 377 samples of lip prints were analysed with Adobe Photoshop software and classified into six different types of lip print patterns, according to Suzuki and Tsuchihashi classifications. Lip prints were divided into six sections including upper left, upper middle, upper right, lower left, lower middle and lower right. Pearson's Chi-square test revealed significant differences between male and female lip prints (p < 0.05) among the Malaysian Malay population of the Klang Valley, with Type V (irregular pattern) lip prints being the most prevalent. In comparison to magnifying glasses, our studies proved the ability to record and examine lip prints utilising a digital approach.